A two-dose heterologous prime-boost vaccine regimen eliciting sustained immune responses to Ebola Zaire could support a preventive strategy for future outbreaks. Issue 2 (1st February 2017) - Shukarev, Georgi; Callendret, Benoit; Luhn, Kerstin; Douoguih, Macaya; ,
ABSTRACT: The consequences of the 2013–16 Ebola Zaire virus disease epidemic in West Africa were grave. The economies, healthcare systems and communities of Guinea, Sierra Leone and Liberia were devastated by over 18 months of active Ebola virus transmission, followed by sporadic resurgences potentially related to sexual transmission by survivors with viral persistence in body fluids following recovery. The need to develop and implement strategies to prevent and mitigate future outbreaks is now beyond dispute. The potential for unpredictable outbreaks of indeterminate duration, and control challenges posed by the possibility of sporadic re-emergence, mean that implementation of an effective vaccination program for outbreak containment necessitates a vaccine providing durable immunity. Heterologous prime-boost vaccine regimens deliver the same or similar antigens through different vaccine types, the first to prime and the second to boost the immune system. Ad26.ZEBOV/MVA-BN-Filo is an investigational Ebola Zaire vaccine regimen that uses this heterologous prime-boost approach. Preliminary Phase 1 data suggest that Ad26.ZEBOV/MVA-BN-Filo confers durable immunity for at least 240 d and is well-tolerated with a good safety profile. This regimen may therefore be suitable for prophylactic use in a regional or targeted population vaccination strategy, and could potentially aid prevention and control of future Ebola outbreaks.